Effect of ablution on methicillin resistant staphylococcus aureus (MRSA) nasal colonization in healthcare workers - Noor Fatima Shoaib; Qurat ul Ain; Khadeja Iqbal; Muhammad Asif (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021